Detection of Organics by FTIR and GC-MS - Mahajan, S.V.; Shrivastava, V.S. (Asian Journal of Chemistry, 2016)
CH2Cl2 extracted samples of the industrial wastes collected from GIDC Vapi and GIDC Ankalshwar (Gujarat) were recorded for IR and GC-MS. Several organic compounds have been found including organophosphorous pesticide. These compounds ultimately affect the soil and ground water quality of the area.